(untitled) (Journal of Biomedical Investigation, 2025)
Background: Foot pain is a common musculoskeletal complaint that can interfere with mobility, daily activities, and clinical performance. Clinical students are particularly vulnerable due to prolonged standing, unsuitable footwear, and heavy Understanding clinical its prevalence associated risk factors is essential for developing effective preventive strategies and improving students’ well-being. Aim: To determine the prevalence of foot pain and identify the associated risk factors among final-year clinical students at the University of Benin. Methods: A descriptive cross-sectional study among 208 final-year clinical students of Physiotherapy, Nursing, Radiography, and Medical Laboratory Science. Participants were selected using a proportionate stratified sampling technique. Data were collected using a validated Foot Health Status Questionnaire (FHSQ). Descriptive statistics summarized the data, while inferential tests (Kruskal Wallis, Mann–Whitney U, Spearman’s correlation, and binary logistic regression) were used to assess associations at a significance level of p < 0.05. Results: The prevalence of foot pain was 47.6% among participants, indicating a moderate to high occurrence. The Kruskal–Wallis test revealed significant differences in foot pain across departments (p=0.019), with nursing students reporting highest scores. Spearman’s correlation showed significant relationships between prolonged standing (r = −0.143, p = 0.039), shoe height (r = −0.166, p = 0.017), and shoe fit (r = 0.157, p = 0.024) with foot pain. The Mann–Whitney U test found no significant gender difference (p = 0.555), while the presence of foot defects significantly influenced foot pain (p = 0.045). Logistic regression showed that the overall model was significant (χ² = 27.74, p = 0.015), though no single predictor independently explained the outcome. Conclusion: Nearly half of the clinical students experienced foot pain, largely associated with prolonged standing, poorly fitted footwear, and pre-existing foot defects.